Inhibition of Erythromycin and Erythromycin-Induced Resistance among Staphylococcus aureus Clinical Isolates - Aya A. Mahfouz; Heba S. Said; Sherin M. Elfeky; Mona I. Shaaban (MDPI AG, 2023)
The increasing incidence of erythromycin and erythromycin-induced resistance to clindamycin among Staphylococcus aureus (S. aureus) is a serious problem. Patients infected with inducible resistance phenotypes may fail to respond to clindamycin. This study aimed to identify the prevalence of erythromycin and erythromycin-induced resistance and assess for potential inhibitors. A total of 99 isolates were purified from various clinical sources. Phenotypic detection of macrolide-lincosamide-streptogramin B (MLSB)-resistance phenotypes was performed by D-test. MLSB-resistance genes were identified using PCR. Different compounds were tested for their effects on erythromycin and inducible clindamycin resistance by broth microdilution and checkerboard microdilution methods. The obtained data were evaluated using docking analysis. Ninety-one isolates were S. aureus. The prevalence of constitutive MLSB, inducible MLSB, and macrolide-streptogramin (MS) phenotypes was 39.6%, 14.3%, and 2.2%, respectively. Genes including ermC, ermA, ermB, msrA, msrB, lnuA, and mphC were found in 82.6%, 5.8%, 7.7%, 3.8%, 3.8%, 13.5%, and 3.8% of isolates, respectively. Erythromycin resistance was significantly reduced by doxorubicin, neomycin, and omeprazole. Quinine, ketoprofen, and fosfomycin combated and reversed erythromycin/clindamycin-induced resistance. This study highlighted the significance of managing antibiotic resistance and overcoming clindamycin treatment failure. Doxorubicin, neomycin, omeprazole, quinine, ketoprofen, and fosfomycin could be potential inhibitors of erythromycin and inducible clindamycin resistance.